Gọi \(A=x^2+y^2+xy-3x-3y-3\)
\(=\left(x^2-2x+1\right)+\left(y^2-2y+1\right)+\left(xy-x-y+1\right)-6\)
\(=\left(x-1\right)^2+\left(y-1\right)^2+\left(x-1\right)\left(y-1\right)-6\)
\(=\left(x-1\right)^2+2\left(x-1\right)\frac{1}{2}\left(y-1\right)+\frac{1}{4}\left(y-1\right)^2+\frac{3}{4}\left(y-1\right)^2-6\)
\(=\left[\left(x-1\right)+\frac{1}{2}\left(y-1\right)\right]^2+\frac{3}{4}\left(y-1\right)^2-6\ge-6\)Có GTNN là -6
Dấu " = " xảy ra \(\Leftrightarrow\hept{\begin{cases}\left[\left(x-1\right)+\frac{1}{2}\left(y-1\right)\right]^2=0\\\frac{3}{4}\left(y-1\right)^2=0\end{cases}\Rightarrow x=y=1}\)
Vậy GTNN của A là -6 tại x = y = 1
A= x2+y2+xy-3x-3y-3
\(=\left[x-1+\frac{1}{2}\left(y-1\right)\right]^2+\frac{3}{4}\left(y-1\right)^2-6\ge-6\)
Dấu "=" xảy ra khi \(\hept{\begin{cases}x-1+\frac{1}{2}\left(y-1\right)=0\\y-1=0\end{cases}\Leftrightarrow}\hept{\begin{cases}x=1\\y=1\end{cases}}\)
Vậy.............